Estudo da descontinuidade geométrica em compósito polimérico reforçado com fibra de juta. - Carlos, Glória Maria Leite (Universidade Federal Rural do Semi-Árido, 2018)
Composites are extremely important materials because of the ability to assign characteristics that a conventional material, in an isolated way, would not be able to provide. With the possibility of adjusting properties, besides, they are associated to the new technological requirements. The present work shows a study about the influence caused by the presence of geometric discontinuity in polymer composites reinforced with jute fibers, evaluating the mechanical properties related to the ultimate strength and modulus of elasticity in a polymer matrix laminate reinforced with bidirectional jute fibers (4 layers), when subjected to uniaxial tensile, under the conditions: original (without the geometric discontinuity) and with geometric discontinuities (central hole of 6 mm and 9 mm), being able to determine how the stress concentration in the jute fiber reinforced with polymer composite interferes in the mechanical properties of the material resulting from the discontinuities. The methodological procedures performed in this work are in accordance with the standards related to uniaxial tensile tests (ASTM D3039), uniaxial tensile tests with geometric discontinuity (ASTM D5766 / D5766M) and density test (ASTM D792). In conclusion, we have presented the laminate that a fragile material behavior to rupture against the uniaxial tension test in all subjected conditions. Regarding the behavior of the fracture of the specimens, all had a final fracture characterized as LGM, according to the standards (ASTM D3039 and ASTM D5766/D5766M).
Monografia
Keywords: Compósitos polimérico; Fibra de juta; Propriedades mecânicas; Descontinuidades geométricas.; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA